Scan : the 419 - Mmobuosi, Kanyinebi Banye (Abuja, Nigeria : Fair Deal Resources Ltd, 2000)
Chronicles how local and international frauds are perpetrated in Nigeria and proffers ideas to detect these malaise after he had analyzed the sociological, spiritual as well as the psychological motives behind the decadent actions.
Includes bibliographic references and index.
oif 09/04/15
Loan
Keywords: Advance fee fraud -- Ngeria; Swindlers and swindling -- Nigeria; Fraud -- Nigeria